2005
DOI: 10.1101/gad.351205
|View full text |Cite
|
Sign up to set email alerts
|

NIR is a novel INHAT repressor that modulates the transcriptional activity of p53

Abstract: Most transcriptional repression pathways depend on the targeted deacetylation of histone tails. In this report, we characterize NIR, a novel transcriptional corepressor with inhibitor of histone acetyltransferase (INHAT) activity. NIR (Novel INHAT Repressor) is ubiquitously expressed throughout embryonic development and adulthood. NIR is a potent transcriptional corepressor that is not blocked by histone deacetylase inhibitors and is capable of silencing both basal and activator-driven transcription. NIR direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
151
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(155 citation statements)
references
References 39 publications
3
151
1
Order By: Relevance
“…NOC2 was shown to be essential for embryonic development in Caenorhabditis elegans (Kamath et al, 2003) and zebra fish (Amsterdam et al, 2004). Interestingly, a human NOC2-containing protein has been identified as an inhibitor of histone acetyltransferase activity (Hublitz et al, 2005).…”
Section: Cloning Of Crc Modifier Genesmentioning
confidence: 99%
“…NOC2 was shown to be essential for embryonic development in Caenorhabditis elegans (Kamath et al, 2003) and zebra fish (Amsterdam et al, 2004). Interestingly, a human NOC2-containing protein has been identified as an inhibitor of histone acetyltransferase activity (Hublitz et al, 2005).…”
Section: Cloning Of Crc Modifier Genesmentioning
confidence: 99%
“…Interestingly, one gene called DKFZp564C186 was also identified in this analysis. This gene attracted our attention as later on it was functionally characterized and renamed as NIR (novel INHAT repressor) (14). To validate the microarray result, we treated CD19ϩ B cells with CD40L plus IL4 and harvested cell lysates at different time points for immunoblot analysis of NIR expression.…”
Section: Expression Of Nir In B Cells and Its Role In B Cellmentioning
confidence: 99%
“…As a nuclear protein, NIR has been shown to directly bind to nucleosomes and core histones and prevent acetylation by histone acetyltransferases. Moreover, NIR also physically interacts with p53 and localizes to the promoter regions of some p53-targeted genes, thus suppressing p53 transcriptional activity and p53-dependent apoptosis (14). We previously found that the expression level of NIR (DKFZp564C186) increased in normal B cells upon stimulation with CD40L plus IL-4 (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, interactions with repressor complexes emerged. 8,23,28 Specifically, there are two categories of genes being repressed: anti-apoptotic [10][11][12][13] and genes active in the G 2 /M phase of the cell cycle. [20][21][22][23] The latter promoters are strongly downmodulated by treatment of cells with DNA-damaging agents, or by p53 overexpression, without any recognizable binding element (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%